Integrasi Ilmu Pengetahuan Dalam Perspektif Filsafat Pendidikan Islam - Azizah Hanum OK; Nurul Amirah; Dicky Armanda (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This journal investigates the concept of knowledge integration in the context of Islamic education, viewed from the perspective of Islamic educational philosophy.  Using philosophical analysis, this paper explores how science can be integrated holistically in the context of Islamic education.  The approach applied is a qualitative method, focusing on data collection and analysis without the need for statistical calculations.  This journal relies on library literature without involving direct observation or interviews, by utilizing various sources of information such as books, academic journals, magazines, newspapers and related literature.  Based on Islamic educational philosophy, the main aim of this paper is to provide a deeper understanding of how to integrate science in the context of Islamic education in accordance with the views of Islamic educational philosophy.